Modeling and Dynamic Optimization of Semi-Batch Acetone–Butanol–Ethanol Fermentation with In-situ Pervaporation Membrane Separations. Issue 4 (2nd October 2017) - Lin, Ta-Chen; Lee, Ya-Hsun
Abstract: To alleviate the severe impact of the substrate and product inhibitions leads to the design of the semi-batch bio-reactors, which aims at finding the optimal control of substrate feed rate through time. The consequence of this problem is challenging, which highlights the numerical difficulties arising from the non-linear, constrained and often discontinuous nature of these dynamic systems. In this work, following the control vector parameterization, a profile generator algorithm is utilized to produce functions in an exponential form that can represent path of the control space comprising elements of both linearity and curvature. A novel method of stochastic dynamic optimization using Simulated Annealing incorporating direct search through a specialized model predictive controller is used to tackle final volume point state constraints. A case study of glucose to acetone–butanol–ethanol production, in terms of structured kinetics model, with in situ pervaporation will be illustrated. Prior to optimization, we proposed revised models based on model identification for the published experimental data in the literature of batch bio-reactor system. Modeling of the pervaporation membrane separations for the system have also been presented. Abstract :